POTENCY OF VIBRIO ISOLATES FOR BIOCONTROL OF VIBRIOSIS IN TIGER SHRIMP (PENAEUS MONODON) LARVAE - WIDANARNI WIDANARNI; A. SUWANTO; SUKENDA SUKENDA; B. W. LAY (BIOTROPIA, 2003)
This study was carried out to obtain Vibrio isolates able to function as biocontrol of vibriosis in shrimp hatchery. Thirty one Vibrio isolates were isolated from tiger shrimp larvae and hatchery environments, i.e. Labuan, Pangandaran, and Lampung, Indonesia. PathogenicÂ  V. harveyi MR5339 was obtained from Maros, South-Sulawesi and was made as a rifampicin resistant mutant (RFR) to screen for those 31 Vibrio isolates in in vitro assays and to allow us to monitor their presence in shrimp larvae and larval rearing water. Almost all VibrioÂ  isolates could inhibit the growth of pathogenic V. harveyi MR5339 RFR. SKT-b isolate from Skeletonema was the most effective to inhibit the growth of V. harveyi MR5339 Rf* and significantly reduced larval mortality in pathogen challenge assays. These prospective biocontrol bacteria, at concentration of 10" CFU/ml, did not show pathogenicity to shrimp larvae. SKT-b was Gram negative, short rod-shape, exhibited yellow colonies on TCBS and swarming on SWC-agar media, motile, utilized glucose and sucrose but not lactose: produced extra-cellular protease and amylase, but did not produce chitmase. Partial sequencing of 16S-rRNA gene SKT-b showed SKT-b similarity to Vibrio alginofyticus. Keywords: shrimp larvae / biocontrol bacteria / vibriosis.